Паганини: Пер. с англ. / Сагден Д. - Сагден Д. (Иллюстрированные Биографии Великих Музыкантов, 1999)
Экземпляры: ИСК (20000726) / Инвентарный номер: 1036266 / Цена: 48.00 / Сис.шифр: 85.315.5 / Авт.знак: С 13 / ГРНТИ: 18 / ББК: 85.315.54